The Role of Green Trust in Mediating the Impact of Green Knowledge, Environmental Concern, and Green Attitude on Tumbler Usage Intention - Siti Sarah Nur Aisyah; Rina Astini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of green knowledge, environmental concern, and green attitude on intention to use environmentally friendly tumblers, with green trust as a mediating variable. The background of this study is based on the gap between the increasing environmental awareness of urban communities and the low adoption of environmentally friendly products such as tumblers. This study uses a quantitative approach with the Partial Least Square - Structural Equation Modeling (PLS-SEM) method processed using SmartPLS 4.1 software, based on data from 100 respondents obtained through distributing online questionnaires by purposive sampling. The results showed that green knowledge and green attitude have a significant effect on intention to use, while environmental concern has no direct effect. Green attitude and environmental concern also have a significant effect on green trust, while green knowledge does not. In addition, green trust is proven to mediate the effect of green attitude and environmental concern on intention to use tumblers, but does not mediate the effect of green knowledge. These findings provide theoretical contributions in the development of pro-environmental behavior models as well as practical implications in the design of educational and promotional strategies to increase the adoption of environmentally friendly products.